Reactive Jump Effect on the Muscle Power of the Educational Center and Exercise of Riau 2018 Dispora Volleyball Student - Juita, Ardiah; Lardika, Rola Angga; Meagalky, Haris Hami (Proceedings of the UR International Conference on Educational Sciences, 2018)
Sports is an effort to maintain a healthy body and is able to improve the function of body organs that are accustomed to exercising. There are many advantages when someone carries out sports activities, besides physical aspects, but also related to social aspects such as adding friends by participating in community sports activities, acknowledging the existence of other people with their willingness to share with their sports friends. The purpose of this study was to find out: the effect of Reactive Jump on the power of athletes leg muscle in the Education and Training Centre of Riau Dispora Volleyball 2018. This type of research was experimental research. The analysis of the t-test yields Tcount of 6,764 and Ttable of 1,753. Means Tcount>Ttable. Based on the t-test after calculating the basis, there is a difference in numbers that increases or rises by 5.01. It can be concluded that Reactive Jump exercises affect the Power of Leg Muscles in PPLP Athletes in Riau Province. Based on the findings and processing of the data above, it can be concluded the following: There is the effect of Reactive Jump (X) exercises with Leg Muscle Power (Y) on PPLP Athletes in Riau Province.